Contemporary Rhinoplasty - Torres Farr, Sebastian (IntechOpen, 2019)
Contemporary Rhinoplasty is a very direct book that presents the procedure from different aspects, giving perspective to the audience. It describes nasal aesthetics, diagnoses, surgical planning, and the learning curve of the procedure for the novel surgeon. It analyses local aspects and technical recommendations for the use of alar rim grafts and gives the reader enough light to understand the complex chapter on saddle nose deformity. It will intersect nasal surgery with morbid conditions such as sleep breathing disorders, clefts, and head and neck cancer. Whatever level of your expertise it will surely add something to your background and enhance your practice.